(untitled) (Update Dental College Journal, 2025)
Introduction: Thalassemia is a haematologic disorder impairing craniofacial development in inadequately treated patients. Research on craniofacial parameters in Bangladeshi thalassemic population comparing to non-thalassemics is scarce. This study aimed to determine the differences in craniofacial parameters if any between thalassemic patients and non-thalassemic individuals in Chattogram, Bangladesh across both sexes. Materials and methods: This cross-sectional analytical study was carried out among 100 respondents (50 transfusion dependent thalassemia patients and 50 non-thalassemic healthy individuals) of 5-30 years during 2020 in Chittagong Medical College, Bangladesh. To measure 10 key craniofacial parameters (head circumference, 6 horizontal and 3 vertical) in cranial, facial, nasal and orbital zones, digital slide caliper and tape were used. To test statistical significance Mann-Whitney U test and unpaired student’s t-test were done as appropriate. Results: The face height of non-thalassemic males was higher than that of thalassemia patients and this was significant (p = 0.027), the intercanthal distance in male with thalassemia showed high significant difference (p= 0.024). When compared to their non-thalassemic peers, thalassemic females patients were observed with significantly larger head circumference (p = 0.025) and head width (p = 0.031). There were differences between the groups in other craniofacial parameters but statistically non-significant (p > 0.05). Conclusion: Distinct differences in craniofacial parameters between thalassemic and non-thalassemic individuals are highlighted which emphasize the impact of thalassemia on craniofacial development, with potential implications for clinical management in thalassemic patients in Bangladesh. Further research is recommended to explore these differences’ underlying mechanisms and broader inferences. Update Dent. Coll. j: 2025; 15(1): 9-14